PEFR, FEF25-75 and MVV In Type-1 Diabetic Male And Their Relationships With HbA1c - Arif, Khan Mohammad; Jahan, Nasim; Sultana, Nayma (Journal of Bangladesh Society of Physiologist, 2013)
Background: Diabetes mellitus is a chronic and debilitating disease. Its complications give rise to microvascular, macrovascular and neuropathic diseases which affect eyes, kidneys, heart, blood vessels and also lungs. So, there may be a relationship between type-1 diabetes and reduced lung function. Objectives: To observe PEFR, FEF25-75 and MVV and their relationship with HbA1c in type- 1 diabetic male in Bangladesh. Methods: This cross-sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka between 1st January and 31st December 2009. A total 30 type-1 diabetic male subjects, age 18-30 years were taken as study group. Another 30 apparently healthy age, sex, BMI and socioeconomic status matched non-diabetic persons were also included as control. For assessment of lung function PEFR, FEF25-75 and MVV of all the subjects were measured by a digital spirometer. Again, to observe glycemic control serum blood glucose and glycosylated hemoglobin (HbA1c) levels of diabetic patients were also measured by usual laboratory technique. Data were analyzed by unpairedt test and Pearsons correlation coefficient test. Results: PEFR (p<0.001), FEF25-75 (p<0.001), and MVV (p <0.001) were significantly lower in type-1 diabetic patients in comparison to those of apparently healthy non-diabetic male. Again, their PEFR (p < 0.05), FEF25-75 (p>0.05), and MVV (p<0.05) were negatively correlated with HbA1c. Conclusion: The lung functions were lower in type-1 diabetic male in comparison to those of non-diabetic counterpart and this reduction is mainly due to poor glycemic control. DOI: http://dx.doi.org/10.3329/jbsp.v8i1.16642 J Bangladesh Soc Physiol. 2013, June; 8(1): 16-20